Neighborhood Characteristics at Birth and Positive and Negative Psychotic Symptoms in Adolescence: Findings From the ALSPAC Birth Cohort - Solmi, Francesca (Schizophr Bull, 2020)
BACKGROUND: Urban birth is associated with risk of non-affective psychoses, but the association with subclinical positive and negative symptoms is less clear, despite emerging evidence. Further the extent to which these findings are confounded by polygenic risk scores (PRS) for schizophrenia is also unknown. METHODS: Using data from the Avon Longitudinal Study of Parents and Children, linked to census geographical indicators, we examined whether various indices of urbanicity at birth were associated with negative and positive psychotic symptoms at age 16 and 18 years, respectively. We used logistic regression models, controlling for child’s ethnicity, maternal age, education, marital status, social class, depressive symptoms, other neighborhood exposures, and, in a subsample of children of white ethnicity (N = 10 283), PRS for schizophrenia. RESULTS: Amongst 11 879 adolescents, those born in the most densely populated tertile had greater odds of reporting positive psychotic experiences, after multivariable adjustment (odds ratio [OR]: 1.57, 95% confidence intervals (CIs): 1.14–2.17). Adolescents born in the most socially fragmented neighborhoods had greater odds of negative symptoms, after multivariable adjustment (OR: 1.43, 95% CI: 1.06–1.85). Although we found that greater schizophrenia PRS were associated with an increased risk of being born in more deprived and fragmented (bot not more densely populated areas), these associations were not confounded by PRS. INTERPRETATION: Birth into more densely populated and socially fragmented environments increased risk of positive and negative psychotic phenomena in adolescence, respectively, suggesting that different forms of neighborhood social adversity may impinge on different psychopathophysiologies associated with the clinical expression of psychosis.